Mechanical and tribological properties of V–C–N coatings as a function of applied bias voltage - Caicedo, J.C.; Gonzalez, R.; Caicedo, H.H.; Gholipourmalekabadi, M.; Amaya, C. (Сверхтвердые материалы, 2016)
The aim of this work is to determine the mechanical and tribological behavior of V–C–N coatings deposited on industrial steel substrates (AISI 8620) by using carbon–nitride coatings as a protective materials. Метою роботи було визначення механічної та трибологічної поведінки V–C–N-покриттів, осаджених на сталеві (AISI 8620) підкладки, для використання як захисні матеріали. Целью работы было определение механического и трибологического поведения V–C–N-покрытий, осажденных на стальные (AISI 8620) подложки, для использования как защитные материалы. This research was supported by Universidad Militar Nueva Granada, contract number ING-1775-2015, Universidad del Quindío and the CIC biomaGUNE, Platform Manager – Surface Analysis and Fabrication, Spain.